Atp13a2 Deficiency Aggravates Astrocyte‐Mediated Neuroinflammation via NLRP3 Inflammasome Activation. (5th February 2016) - Qiao, Chen; Yin, Nuo; Gu, Huan‐Yu; Zhu, Jia‐Lei; Ding, Jian‐Hua; Lu, Ming; Hu, Gang
Summary: Aim: Atp13a2 (Park9) gene encodes a transmembrane lysosomal P5‐type ATPase (ATP13A2), and its missense or truncation mutations leads to lysosomal dysfunction and consequently results in neuronal death in the pathogenesis of Parkinson's disease (PD). Nevertheless, the roles of ATP13A2 in the biological features of astrocytes, especially in the regulation of PD‐related neuroinflammation, have not been investigated. Methods: We cultured primary neurons and astrocytes from mouse midbrain to investigate the mechanisms for astrocyte ATP13A2‐regulated lysosomal function and neuroinflammation following 1‐methyl‐4‐phenylpyridinium (MPP + ) treatment. Results: We found that astrocytes expressed considerable levels of ATP13A2 and deficiency of ATP13A2 in astrocyte‐induced intense inflammation, which exacerbated dopaminergic neuron damage after exposure to MPP + . Notably, lack of ATP13A2 increased lysosomal membrane permeabilization and cathepsin B release, which in turn exacerbated activation of nod‐like receptor protein 3 (NLRP3) inflammasome to produce excess IL‐1 β from astrocytes. Furthermore, overexpression of ATP13A2 reversed MPP + ‐induced cathepsin B release and NLRP3 inflammasome activation in astrocytes. Conclusions: Our results have revealed a novel role of ATP13A2 in modulating astrocyte‐mediated neuroinflammation via NLRP3 inflammasome activation, thus bringing to light of a direct link between astrocyte lysosome and neuroinflammation in the pathological model of PD.